T cell depleted haploidentical transplantation: positive selection - Franco Aversa (MDPI AG, 2011)
Interest in mismatched transplantation arises from the fact that a suitable one-haplotype mismatched donor is immediately available for virtually all patients, particularly for those who urgently need an allogenic transplant. Work on one haplotype-mismatched transplants has been proceeding for over 20 years all over the world and novel transplant techniques have been developed. Some centres have focused on the conditioning regimens and post transplant immune suppression; others have concentrated on manipulating the graft which may be a megadose of extensively T celldepleted or unmanipulated progenitor cells. Excellent engraftment rates are associated with a very low incidence of acute and chronic GVHD and regimen-related mortality even in patients who are over 50 years old. Overall, event-free survival and transplant-related mortality compare favourably with reports on transplants from sources of stem cells other than the matched sibling.